Nitrogen budgets of the Long Island Sound estuary. (5th January 2020) - Vlahos, Penny; Whitney, Michael M.; Menniti, Christina; Mullaney, John R.; Morrison, Jonathan; Jia, Yan
Abstract: Nitrogen (N) inputs to coastal ecosystems have significant impacts on coastal community structure. In N limited systems, increases in N inputs may lead to excess productivity and hypoxia. Like many temperate estuaries, Long Island Sound (LIS), a major eastern U.S. estuary, is a N limited system which has experienced seasonal hypoxia since the 1800s. This study is the first effort to constrain the total N cycle in this estuary. The approach utilizes data collected over the last two decades in the LIS time series with hydrodynamic model results to generate both monthly and annual N budgets between 1995 and 2016. Of the total N that is delivered to LIS through rivers and atmospheric inputs, 40% is exported to the adjacent continental shelf on the order of 10.8 ± 8.9 × 10 6  kg N/year. Of this export, 41% is dissolved organic N, 29% is particulate organic N, 32% is nitrate + nitrite, and −3% is ammonium. The remaining 60% of the N delivered to LIS is either buried in sediments or lost through denitrification. This inferred internal loss rate is equivalent to 5.4 g N/(m 2 year). This study serves as an example of the significant inter-annual variations that estuarine budgets undergo as efforts to understand coastal biogeochemical cycles move forward. Highlights: First nitrogen(N) budgets for Long Island Sound (LIS). 60% of N entering LIS is buried or denitrified. 40% of N is exported to coastal ocean. LIS is a net exporter of N though inter annual variation is large. Seasonally LIS can be either a net importer or exporter of N.